Analysis Of The Advertising Effectiveness Of The Management Study Program Of The Darmajaya Institute Of Informatics And Business Through Instagram With An Approach Customer Response Index (CRI) - Muhammad Rafiq; Betty Magdalena; Viola De Yusa (SEAN Institute, 2024)
Analysis of Advertising Effectiveness Through Instagram in the Management Study Program IIB Darmajaya with the Customer Response Index (CRI) Approach aims to identify the success of advertising carried out by the Management Study Program at IIB Darmajaya through the Instagram social media platform. This study uses two important analytical frameworks, namely the Customer Response Index (CRI) to evaluate the competitive position of the study program in the use of Instagram as a marketing tool. CRI helps in assessing the relative position of the study program compared to its competitors in the realm of social media. Through this methodology, the study will explore the effectiveness of advertising campaigns carried out on Instagram. Overall, the results show that, while marketing strategies have been successful in creating awareness and understanding, there is room for improvement in increasing interest and turning intentions into tangible actions. For this reason, a more in-depth analysis of the factors that cause obstacles in the conversion process is needed, so that marketing strategies can be adjusted to improve the performance of study programs in the market.